Amyloid in skin and brain: what′s the link? - Schreml, Stephan; Kaiser, Elmar; Landthaler, Michael; Szeimies, Rolf-Markus; Babilas, Philipp (Experimental dermatology, 2010)
Abstract: For too long, amyloids have been under general suspicion to merely cause diseases. In recent years, we have learned that these interesting proteins may also fulfill important biological tasks. Moreover, recent publications show emerging evidence for a so-called brain-skin axis. This viewpoint paper aims to address the question what is known about the link between brain and skin based on the literature available for two diseases caused by amyloid formation: Alzheimer′s disease (AD) and cutaneous amyloidoses. In addition, we acquaint the reader with a different perspective on the role of amyloid in skin and brain.